Improvement of Durability and Service Life of Concrete Using Class F Fly Ash - Nath, Pradip; Sarker, Prabir (The Concrete Institute of Australia, 2011)
Durability is one of the primary considerations in designing concrete structures, especially when used in aggressive environment. Various supplementary cementitious materials (SCM) can be used to improve durability properties of concrete. However, the degree of improvement is dependent on the type of SCM and the mixture proportions of the concrete. In this study, Class F fly ash sourced from Western Australia was used as 30% and 40% of the total binder. The chloride diffusion properties of concrete containing fly ash were compared with those of control concrete. Fly ash concretes that were designed with adjusted water to binder ratio and total binder content to achieve similar 28-day compressive strength of the control concrete showed less chloride diffusion as compared to the control concrete. Simple deterministic service life estimation technique using the well known Fick’s law was applied to assess the service life of concrete mixes against the corrosion due to chloride diffusion. Early age properties were used along with certain selected parameters to predict the service life of concrete. Fly ash concretes resulted in higher service life than the control concrete when chloride diffusion was considered as the dominant form of attack.